Directionality models from ground motions of Italy - Pinzón Ureña, Luis (2018)
Directionality effects on the expected strong ground motion in Italy are investigated. After a brief description of the directionality effect and the intensity measures involved, a wide Italian database1 of strong ground motion records is used, with a total of 949 horizontal accelerograms (two components). The analysis is performed for 5% damped response spectra in the 0.01-4 s period range. Rotation-independent intensity measures, resulting from combining maximum values of the as-recorded accelerograms, are investigated. The study has also been performed using maximum values of the time histories resulting from the previous combination of as-recorded time histories. Ratios between these rotation-independent intensity measures and those formerly used in ground motion predictive equations have been computed and modelled by means of a simple theoretical model. Thus, the results are useful for updating former strong ground motion predictive equations in a simple and straightforward way.